Experiment investigation of hole accuracy and surface roughness in femur bone drilling using different parameters - Ndaruhadi, P.; Sharif, S.; Kurniawan, Denni (2014)
Success indicators in bone drilling include clean, good accuracy drilled holes without damage at the surrounding tissue. This study investigates the influence of cutting parameters in bone drilling against hole accuracy (enlargement diameter, circularity error, and cylindricity error) and surface roughness (Ra). A series of bone drilling experiments was carried out using femur bovine bone and without irrigation. Variations of drill type (high speed steel and coated and uncoated carbide) and cutting speed (19 m/min and 94 m/min) were used as input variables, while the feed rate (0.025 mm/rev) was constant. It was found that coated carbide drill results minimum magnitude on all machining responses. Type of tool gives significant effect on diameter enlargement and surface roughness, yet not on circularity and cylindricity errors. The range of cutting speed evaluated does not give significant effect on any surface integrity measures. © (2014) Trans Tech Publications, Switzerland.